Creating learning opportunities for pharmacy students through an observership program. - Nguyen, Kimberly A.; Hart, Sara R.; Pidcock, Kathryn N.; Sampson, Earl F. (American Journal of Health-System Pharmacy, 2012)
Purpose. The development, implementation, challenges, and future opportunities associated with a pharmacy observership program are described. Summary. In the summer of 2010, the pharmacy observership committee at The Methodist Hospital created a formalized, institution-based pharmacy observership program to introduce first-and second-year pharmacy students to the diverse areas of pharmacy practice. The two-month experience includes opportunities for students to participate in various departmental research projects and to observe the responsibilities of pharmacy staff. Four students have completed the observership program thus far. All observers commented that the program was a valuable introduction to hospital pharmacy. Feedback was obtained from the observers and each preceptor. Limitations of the program include a lack of funding for parking and lodging expenses, a lack of pagers, and a lack of a stipend for the observers. Although there was not an established budget for the program, our perceived costs were approximately $10,000. Conclusion. An observership program was established to allow first- and second-year pharmacy students to gain exposure to various aspects of hospital pharmacy outside of a formal internship.